2023
DOI: 10.1111/ene.15779
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of arterial blood gas parameters as prognostic markers in amyotrophic lateral sclerosis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Cox univariate analysis of FVC% confirmed that this measure is a strong predictor of survival [28], even when it is considered as ΔFVC%. In the Milan MND cohort, Cox univariate analysis of individual ABG parameters showed a significantly increased HR, and consequentially a shorter survival time in MND patients, when pCO 2 was >45 mmHg, HCO3 was >24 mmol/L and SBE was >2 mmol/L, confirming the prognostic role of ABG parameters [13, 29]. Interestingly, when considering ABG measurements individually, HCO3 was found to be the measurement with the earliest changes associated with a worse prognosis, being a negative prognostic factor when it increased above 24 mmHg, which is widely considered within reference limit values.…”
Section: Discussionmentioning
confidence: 88%
“…Cox univariate analysis of FVC% confirmed that this measure is a strong predictor of survival [28], even when it is considered as ΔFVC%. In the Milan MND cohort, Cox univariate analysis of individual ABG parameters showed a significantly increased HR, and consequentially a shorter survival time in MND patients, when pCO 2 was >45 mmHg, HCO3 was >24 mmol/L and SBE was >2 mmol/L, confirming the prognostic role of ABG parameters [13, 29]. Interestingly, when considering ABG measurements individually, HCO3 was found to be the measurement with the earliest changes associated with a worse prognosis, being a negative prognostic factor when it increased above 24 mmHg, which is widely considered within reference limit values.…”
Section: Discussionmentioning
confidence: 88%
“…In other ALS cohorts, MVV has already been shown to have good correlations with other PFTs, such as FVC, slow vital capacity (SVC), FEV1, SNIP, phrenic nerve amplitude, peak expiratory flow (PEF), and total ALSFRS-R [20]. Recent studies examining independent cohorts [12,13,31] have agreed upon the role of blood carbonate (HCO 3 − ) and base excess (BE) in evaluating early respiratory failure phenomena such as nocturnal hypoventilation, and we also observed a moderate correlation of cMVV with these two ABGs measures.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, consulting the most updated international guidelines on mechanical ventilation [5][6][7][8], there is no international consensus on the best timing for non-invasive ventilation (NIV) adaptation. Thirdly, although forced vital capacity (FVC) is the most commonly used pulmonary function test and outcome measure in clinics, many other respiratory measures, such as nocturnal oximetry [9], capnography [10], sniff nasal inspiratory pressure (SNIP) [11], and arterial blood gas analysis (ABGs) [12,13] have shown high reliability in detecting early signs of respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Given that respiratory failure is the main cause of mortality in ALS, measurements of respiratory functionality are integrated not only in clinical practice, but also in ALS prognostic models [ 12 , 242 ]. However, more recent studies have highlighted that not only slow (SVC) or forced vital capacity (FCV) [ 243 ] may be a useful prognostic marker but that other parameters such as arterial blood gas parameters and base excess may independently predict shorter survival in ALS [ 244 , 245 ]. Within this context, a recent neurophysiological study pointed out that Diaphragmatic CMAP amplitude from phrenic nerve stimulation may also be able to predict functional decline in ALS [ 246 ].…”
Section: Prognosismentioning
confidence: 99%